Identifying the determinants of hospital readmission in dementia patients – A retrospective cohort study using electronic healthcare records in England - Bria Browne; Imogen Rogers; Khalid Ali; Naji Tabet; Elizabeth Ford (PLoS ONE, 2026)
Background People living with dementia are at an increased risk of multiple hospital admissions due to acute illness, underlying vulnerability, progression of behavioural symptoms of dementia, or breakdown of care provision. Reducing readmission rates is a key clinical priority. This study used linked electronic health records from general practice and hospitals in England, to investigate the determinants associated with hospital readmissions and estimate the mortality risk of older adults with dementia within one year of hospital readmission. Methods A retrospective cohort study using Clinical Practice Research Datalink and linked data. Patients were included if they were > 65y, diagnosed with dementia, and had a recorded acute general hospital admission. Outcome variables were readmission to hospital within 180 days of discharge, and in the readmitted group, mortality within one year of readmission. Demographics, long term conditions, polypharmacy, antipsychotic medication, medication review, post-discharge primary care appointments, and living in residential care were examined as determinants using stepwise logistic regression for readmission, and Cox regression for survival models. Results 30,527 patients were included, median age 84y (62.7% female), with 12,351 (40.5%) readmitted within 180 days of discharge. Being male, having multiple long-term conditions, having a medication review or attending a primary care appointment post-discharge were positively associated with readmissions, while Alzheimer’s type dementia, having ‘Other’ ethnicity, and living in residential care were negatively associated. We found a significant effect on mortality risk of age, sex, type of dementia, having two or more long-term conditions, body mass index, antipsychotic medication, polypharmacy, and living in residential care. Conclusion The findings of this cohort study suggest that biological, psychological, and social factors interact to influence hospital readmissions in older adults with dementia. Multiple long-term conditions emerged as the strongest determining factor for readmission, while age was important in survival. Future research should assess psychosocial factors such as social support, caregiver burden, and mental well-being. These findings have important implications for strengthening community-based healthcare for adults with dementia, to reduce hospital readmission.